A ceramic-coated separator dedicated to lithium metal batteries

CN122843703BActive Publication Date: 2026-11-03宁波大浦新材料科技有限公司 +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611339371.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-09-01
Publication Date
2026-11-03
Estimated Expiration
2046-09-01

AI Technical Summary

Technical Problem

Existing ceramic-coated separators are ineffective in addressing the interface problems of lithium metal anodes in lithium metal batteries. This leads to irregular protrusions of lithium metal during deposition, which can penetrate the separator and cause short circuits in the battery. Furthermore, the lack of stress relief mechanisms results in coating cracking and pulverization, affecting the battery's cycle stability and safety.

Method used

A composite ceramic coating is applied to the surface of a porous polymer-based membrane. The coating has a two-layer gradient structure, including a highly elastic buffer layer and a highly rigid protective layer. By introducing an elastic polymer binder and specific inorganic fillers, a labyrinth structure is constructed using high-shear peeling and slit extrusion coating processes to achieve a smooth transition of mechanical properties and uniform lithium deposition.

Benefits of technology

It effectively absorbs the compressive stress of negative electrode volume expansion, inhibits uneven lithium metal deposition, improves the mechanical protection and electrochemical stability of the battery, and enhances the barrier performance and cycle life of the separator.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a ceramic-coated diaphragm special for a lithium metal battery, belongs to the field of lithium metal batteries, and comprises a porous polymer base film, wherein one side surface of the porous polymer base film is provided with a composite ceramic coating layer; the composite ceramic coating layer is a double-layer gradient structure, and comprises a high-elasticity buffer layer in contact with the surface of the porous polymer base film and a high-rigidity protective layer located on the surface of the high-elasticity buffer layer and away from the porous polymer base film; the high-elasticity buffer layer is formed by coating and drying a first ceramic slurry, and the high-rigidity protective layer is formed by coating and drying a second ceramic slurry; the inner high-elasticity buffer layer composed of an elastic polymer binder is introduced, can effectively absorb the compressive stress generated by the volume expansion of a negative electrode, and proves that the buffer layer acts as a stress absorption valve, and the effect is similar to that of a stress absorption valve, so that the mechanical mismatch problem between the rigid layer and the flexible base film is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium metal batteries, specifically to a ceramic-coated separator for lithium metal batteries. Background Technology

[0002] With the rapid development of high-energy-density secondary battery technology, lithium metal batteries have become a research focus of the next generation of energy storage devices due to their extremely high theoretical specific capacity and extremely low electrolyte potential. In the actual application scenarios of lithium metal batteries, the traditional battery separator system faces severe challenges due to the drastic interface evolution of the lithium metal anode during charging and discharging.

[0003] Currently, existing ceramic-coated separators mainly employ a method of coating a single layer of inorganic particles onto the surface of a polymer-based membrane. However, in actual operation, this traditional structure is difficult to cope with the unique interface problems of lithium metal batteries. Lithium metal is prone to generating irregular protrusions during deposition, and existing single-layer ceramic coatings often lack sufficient physical barrier strength and directional guidance of microstructure, allowing these protrusions to easily penetrate the separator and cause internal short circuits in the battery.

[0004] Lithium metal anodes undergo significant volume changes during cycling. The mechanical properties of traditional ceramic coatings and polymer base films differ considerably. Due to the lack of effective stress relief mechanisms, the coatings are prone to cracking, pulverizing, or even large-scale detachment from the base film surface under frequent volume expansion and contraction stresses. This physical failure not only leads to an abnormal increase in interfacial impedance but also causes the base film to lose its protection, resulting in a significant decline in the cycle stability and coulombic efficiency of the battery.

[0005] In addition, existing technologies have limited effectiveness in improving lithium-ion flow distribution and cannot effectively suppress the unevenness of metallic lithium in the early stage of deposition. Under complex electrochemical environments, ion transport at the interface is extremely unstable, which can easily induce abnormal loss of active materials, seriously affecting the safe operation and service life of the battery.

[0006] The information disclosed in the background section above is only intended to enhance the understanding of the background of this disclosure, and therefore may include information that does not constitute prior art known to those skilled in the art. Summary of the Invention

[0007] The purpose of this invention is to provide a ceramic-coated separator specifically for lithium metal batteries, in order to solve the problems mentioned in the background art.

[0008] The technical solution of the present invention includes a porous polymer base membrane, wherein a composite ceramic coating is provided on one side surface of the porous polymer base membrane; the composite ceramic coating is a two-layer gradient structure, including a highly elastic buffer layer in contact with the surface of the porous polymer base membrane, and a highly rigid protective layer located on the surface of the highly elastic buffer layer and away from the porous polymer base membrane; the highly elastic buffer layer is formed by coating and drying a first ceramic slurry, and the highly rigid protective layer is formed by coating and drying a second ceramic slurry.

[0009] Preferably, the thickness of the highly elastic buffer layer is 3-8µm; the thickness of the highly rigid protective layer is 1-4µm.

[0010] Preferably, by weight, the first ceramic slurry comprises: 5-15 parts of elastic polymer binder, 85-95 parts of first inorganic filler, and 100-400 parts of solvent; wherein the total of the elastic polymer binder and the first inorganic filler is 100 parts by weight; and by weight, the second ceramic slurry comprises: 3-8 parts of rigid polymer binder, 92-97 parts of second inorganic filler, 0.5-3 parts of lithiophilic modifier, and 100-400 parts of solvent.

[0011] Preferably, the elastic polymer binder is selected from one or more of styrene-butadiene rubber, hydrogenated nitrile rubber, and thermoplastic polyurethane; the rigid polymer binder is selected from one or more of polyvinylidene fluoride and polyimide.

[0012] Preferably, the first inorganic filler is selected from one or more of mesoporous silica, fumed alumina, and boehmite, and the average particle size of the first inorganic filler is 100-500 nm; the second inorganic filler is selected from one or more of boron nitride nanosheets and sheet alumina, and the second inorganic filler is a nanosheet structure with an aspect ratio greater than 30 obtained after liquid phase exfoliation and centrifugal classification; the lithiophilic modifier is selected from one or more of zinc oxide, titanium dioxide, and lithium nitride, and the lithiophilic modifier is a nanoparticle grown in situ or coated on the surface of the second inorganic filler by sol-gel method or hydrothermal synthesis.

[0013] Preferably, the second inorganic filler comprises boron nitride nanosheets and sheet-like alumina, and the mass ratio of the boron nitride nanosheets to the sheet-like alumina is (1:1)-(2:1).

[0014] Preferably, the porous polymer base membrane is selected from one or more of polyethylene film and cellulose nonwoven fabric, and the thickness of the porous polymer base membrane is 10-25µm.

[0015] Preferably, the high-elasticity buffer layer is formed by coating and drying the first ceramic slurry after high-speed stirring and ball milling using a microgravure coating process; the formation process of the high-rigidity protective layer includes: firstly, dispersing the raw material of the second inorganic filler under high shear to obtain a sheet-like structure with an aspect ratio greater than 30; the lithium-affinity modifier is zinc oxide, titanium dioxide, or lithium nitride nanoparticles grown in situ or coated on the surface of the second inorganic filler by sol-gel method or hydrothermal synthesis method; the second inorganic filler with lithium-affinity modifier on the surface and the rigid polymer binder are subjected to high-speed stirring and ultrasonic dispersion treatment to obtain the second ceramic slurry, which is then coated and dried using a slot extrusion coating process.

[0016] Preferably, the drying temperature of the high-elasticity buffer layer is 80-100℃; the drying temperature of the high-rigidity protective layer is 90-110℃.

[0017] This invention provides an improved ceramic-coated separator specifically for lithium metal batteries, which has the following improvements and advantages compared to the prior art:

[0018] 1. This invention introduces an inner high-elasticity buffer layer composed of an elastic polymer binder, which can effectively absorb the compressive stress generated by the volume expansion of the negative electrode. This proves that the buffer layer acts as a stress absorption valve and solves the mechanical mismatch problem between the rigid layer and the flexible base film.

[0019] 2. By growing a lithiophilic modifier on the filler surface through in-situ reaction modification, chemical bonding level dispersion was achieved. The lithiophilic sites effectively reduced the lithium nucleation overpotential, guided the uniform deposition of lithium metal, and suppressed interface failure. Detailed Implementation

[0020] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments.

[0021] Example 1

[0022] This invention provides a ceramic-coated separator for lithium metal batteries, comprising a porous polymer base membrane, wherein a composite ceramic coating is provided on one side surface of the porous polymer base membrane; in this embodiment as the preferred implementation mode, a polyethylene membrane is selected as the porous polymer base membrane, with a thickness of 10µm and a porosity of 40%; due to its good chemical stability and mechanical strength, the polyethylene membrane provides a basic supporting framework for the composite separator.

[0023] The composite ceramic coating has a two-layer gradient structure, including a highly elastic buffer layer in contact with the surface of the porous polymer base film, and a highly rigid protective layer located on the surface of the highly elastic buffer layer and away from the porous polymer base film. This two-layer gradient design is not a simple physical stacking, but is based on the principle of modulus matching: the inner low-modulus region is used to absorb the compressive stress generated by the volume expansion of the negative electrode, and the outer high-modulus region is used to resist the stress concentration at the tip, thereby achieving a smooth transition of mechanical properties at the microscale.

[0024] The highly elastic buffer layer is formed by coating and drying a first ceramic slurry with a thickness controlled at 3µm. At this thickness, the coating can provide sufficient buffer space without excessively increasing the transport path length of lithium ions.

[0025] The high-elasticity buffer layer is formed by coating and drying the first ceramic slurry after high-speed stirring and ball milling using a microgravure coating process; the drying temperature is set at 80℃; the microgravure coating process utilizes its unique reverse shearing action to ensure that the first ceramic slurry can fully penetrate the surface pores of the polyethylene base membrane, enhancing the interlayer bonding force; by weight, the first ceramic slurry includes: 5 parts of elastic polymer binder, 95 parts of first inorganic filler, and 100 parts of solvent; wherein, the elastic polymer binder is styrene-butadiene rubber, and the first inorganic filler is fumed alumina with an average particle size of 100nm; the high-elasticity segments of styrene-butadiene rubber endow the buffer layer with excellent deformation recovery ability, preventing the peeling of the active material layer from the membrane interface.

[0026] The high-rigidity protective layer is formed by coating and drying a second ceramic slurry with a thickness controlled at 1µm. This extremely thin thickness design aims to reduce the battery's internal resistance.

[0027] The formation process of the high-rigidity protective layer includes: firstly, the raw material of the second inorganic filler is subjected to high-shear exfoliation and dispersion to obtain a specific aspect ratio; then, the precursor of the lithium-affinity modifier is introduced for in-situ reaction modification; finally, the second ceramic slurry is prepared by high-speed stirring and ultrasonic dispersion with a rigid polymer binder; the slurry is coated and dried using a slot extrusion coating process; the drying temperature is set to 90℃.

[0028] The high-shear exfoliation dispersion step utilizes strong fluid shear force to exfoliate layered raw materials into fewer-layer nanosheets, ensuring that the aspect ratio meets the requirements for constructing a maze structure; the in-situ reaction modification involves directly growing functional particles on the surface of the nanosheets. Compared with physical mixing, this chemical bonding method significantly improves the uniformity and stability of the modifier distribution.

[0029] The slit extrusion coating process induces the horizontal alignment of sheet-like fillers through the directional flow field at the slit outlet; this ensures that the coating head shear rate is maintained at 200-450 s. -1In this embodiment, the key process parameters are specifically set: the coating line speed is set to 5 m / min, the die lip clearance of the slit die head is set to 250 µm, and the effective shear rate calculated based on the formula is approximately 333 s. -1 The specific calculation formula is as follows: ;in, Let v be the shear rate, g be the coating line speed, and g be the die lip clearance of the slit die. A closed-loop feedback system consisting of an online viscometer and a precision metering pump is used to control the material supply stability, thereby achieving precise control of the shear rate in actual operation. To demonstrate the specific differences in the impact of different rates within a set range on the orientation degree and final performance, this embodiment further demonstrates the effect of 200 s on the orientation degree and final performance. -1 and 450 s -1 A comparative experiment was conducted at two shear rate points.

[0030] The results show that when the shear rate is 200 s... -1 At that time, the horizontal orientation degree of the lamellar filler in the coating, I002 / I100, was 65.4, corresponding to a dendrite penetration limiting current of 7.8 mA / cm²; when the shear rate increased to 450 s⁻¹, the horizontal orientation degree of the lamellar filler was 65.4, corresponding to a dendrite penetration limiting current of 7.8 mA / cm². -1 At this time, the orientation degree significantly increased to 91.2, and the limiting current reached 9.4 mA / cm²; as a control, if the shear rate is below the lower limit of the interval, such as 100 s, the orientation degree increased significantly ... -1 The orientation degree was only 28.5, and the limiting current dropped to 5.5 mA / cm²; this set of data fully confirms the 200-450 s -1 The shear rate within the range can effectively induce the orientation of the filler, thereby significantly improving the barrier performance of the diaphragm.

[0031] By weight, the second ceramic slurry comprises: 3 parts rigid polymer binder, 96.5 parts second inorganic filler, 0.5 parts lithiophilic modifier, and 100 parts solvent; wherein, the rigid polymer binder is polyvinylidene fluoride; the second inorganic filler is boron nitride nanosheets and sheet-like alumina in a mass ratio of 1:1; the lithiophilic modifier is zinc oxide, which is nanoparticles grown in situ on the surface of the filler by the sol-gel method; the lithiophilic sites provided by zinc oxide effectively reduce the nucleation overpotential of lithium ions, guide the uniform deposition of lithium metal, and inhibit dendrite germination.

[0032] Example 2

[0033] This embodiment provides a ceramic-coated separator specifically for lithium metal batteries, which is another specific implementation based on the technical solution of Embodiment 1; the thickness of the high-elasticity buffer layer is 3-8µm; the thickness of the high-rigidity protective layer is 1-4µm; in this embodiment, the thickness of the high-elasticity buffer layer is specifically adjusted to 5µm, and the thickness of the high-rigidity protective layer is specifically adjusted to 2.5µm; the base film is a polyethylene film with a thickness of 16µm; this thickness combination aims to balance the energy density and safety protection performance of the battery, and is suitable for energy storage lithium metal batteries with higher requirements for cycle life.

[0034] By weight, the first ceramic slurry comprises: 5-15 parts of an elastic polymer binder, 85-95 parts of a first inorganic filler, and 100-400 parts of a solvent; the elastic polymer binder is selected from one or more of styrene-butadiene rubber, hydrogenated nitrile rubber, and thermoplastic polyurethane.

[0035] The first inorganic filler is selected from one or more of mesoporous silica, fumed alumina and boehmite, and the average particle size of the first inorganic filler is 100-500 nm. Specifically, the first ceramic slurry includes: 10 parts of elastic polymer binder, 90 parts of the first inorganic filler and 250 parts of solvent. Among them, the elastic polymer binder is hydrogenated nitrile rubber, whose excellent chemical corrosion resistance ensures long-term bonding stability in the electrolyte immersion environment.

[0036] The first inorganic filler is mesoporous silica with an average particle size of 200 nm. The unique pore structure of mesoporous silica can not only adsorb electrolyte and improve ionic conductivity, but also serve as a micro reservoir to alleviate localized electrolyte deficiency during circulation.

[0037] By weight, the second ceramic slurry comprises: 3-8 parts of rigid polymer binder, 92-97 parts of second inorganic filler, 0.5-3 parts of lithiophilic modifier, and 100-400 parts of solvent; the rigid polymer binder is selected from one or more of polyvinylidene fluoride and polyimide; the second inorganic filler is selected from one or more of boron nitride nanosheets and sheet alumina, and the second inorganic filler is a nanosheet structure with an aspect ratio greater than 30 obtained after liquid phase exfoliation and centrifugal classification.

[0038] The aspect ratio was obtained by observing at least 50 nanosheet structures using a scanning electron microscope and calculating their average value; the lithiophilic modifier was selected from one or more of zinc oxide, titanium dioxide and lithium nitride, wherein the precursor of the lithium nitride was selected from lithium amino or lithium methyl, and was generated by pyrolysis-assisted in-situ conversion under a nitrogen atmosphere; the lithiophilic modifier was nanoparticles grown in situ or coated on the surface of the second inorganic filler by sol-gel method or hydrothermal synthesis.

[0039] Specifically, the second ceramic slurry comprises: 5 parts of a rigid polymer binder, 93 parts of a second inorganic filler, 2 parts of a lithiophilic modifier, and 250 parts of a solvent. The rigid polymer binder is polyimide, which utilizes its extremely high heat resistance to improve the structural integrity of the membrane under thermal runaway critical conditions. The second inorganic filler comprises boron nitride nanosheets and sheet-like alumina in a mass ratio of 1.5:1, with aspect ratios controlled above 30. The lithiophilic modifier is titanium dioxide, which is in-situ coated using a hydrothermal synthesis method. Titanium dioxide has a strong interaction with lithium ions, which can homogenize the interfacial lithium ion flow and prevent dendrite piercing caused by excessively rapid local deposition. In this embodiment, the comprehensive electrochemical performance and thermal safety of the membrane are improved by introducing heat-resistant components and mesoporous materials.

[0040] Example 3

[0041] This embodiment provides a ceramic-coated separator specifically for lithium metal batteries, which is another specific implementation based on the technical solution of Embodiment 1; the porous polymer base membrane is selected from one or more of polyethylene membrane and cellulose nonwoven fabric, and the thickness of the porous polymer base membrane is 10-25µm; in this embodiment, cellulose nonwoven fabric is selected as the base membrane, and the thickness is 25µm; cellulose nonwoven fabric has natural hydrophilicity and excellent heat shrinkage resistance, which can further improve the battery's liquid absorption capacity and high-temperature safety.

[0042] The second inorganic filler includes boron nitride nanosheets and plate-shaped alumina, and the mass ratio of boron nitride nanosheets to plate-shaped alumina is (1:1)-(2:1). In the high-rigidity protective layer of this embodiment, the mass ratio of boron nitride nanosheets to plate-shaped alumina is set to 2:1. Increasing the proportion of boron nitride utilizes its extremely high in-plane thermal conductivity, which helps to quickly dissipate the local Joule heat at the deposition site, reduce the hot spot temperature, and thus suppress the accelerated dendrite growth induced by local high temperature.

[0043] Furthermore, in this embodiment, the thickness of the highly elastic buffer layer is 8µm, using 15 parts of thermoplastic polyurethane as a binder, combined with 85 parts of boehmite with an average particle size of 500nm. The thicker buffer layer and the highly elastic polyurethane work synergistically, specifically designed for lithium metal anodes with high areal capacity and large volume expansion, ensuring that the separator structure does not undergo brittle fracture during deep charge-discharge cycles. The thickness of the high-rigidity protective layer is 4µm, using lithium nitride as the lithiophilic modifier, 3 parts, grown in situ via the sol-gel method. Lithium nitride has extremely high lithium-ion conductivity, serving as a fast ion conductor channel and effectively reducing interfacial impedance. This embodiment focuses on solving the problems of thermal management and large strain adaptability in high-energy-density batteries.

[0044] Example 4

[0045] This embodiment provides a ceramic-coated separator specifically for lithium metal batteries, which is another specific implementation based on the technical solution of Embodiment 1; this embodiment aims to explore the synergistic effect of mixed components; the base membrane is a 12µm polyethylene membrane.

[0046] The elastic polymer binder is selected from one or more of styrene-butadiene rubber, hydrogenated nitrile butadiene rubber, and thermoplastic polyurethane. In the high elasticity buffer layer of this embodiment, the elastic polymer binder is a mixture of styrene-butadiene rubber and hydrogenated nitrile butadiene rubber in a 1:1 mass ratio, totaling 8 parts. This mixed system combines the high elasticity of SBR with the high adhesion of HNBR, balancing the cohesive strength and interfacial adhesion of the coating. The first inorganic filler is a mixture of fumed alumina and boehmite in a 1:1 ratio, totaling 92 parts, with an average particle size of 300 nm. The coating thickness is 4 µm, and the drying temperature is 85 °C.

[0047] The rigid polymer binder is selected from one or more of polyvinylidene fluoride and polyimide; in the high rigidity protective layer of this embodiment, the rigid polymer binder is polyimide, 4 parts; the mass ratio of boron nitride nanosheets to sheet alumina in the second inorganic filler is 1.2:1, 94.5 parts; the lithiophilic modifier is zinc oxide, 1.5 parts; the coating thickness is 2µm, and the drying temperature is 95℃; by mixing fillers with different particle sizes and morphologies, this embodiment constructs a more compact particle packing structure, further tortuous the pore path, and delays the physical penetration rate of dendrites to the maximum extent without sacrificing ion flux, demonstrating the robustness of the formulation design.

[0048] Example 5

[0049] This embodiment provides a ceramic-coated separator specifically for lithium metal batteries, which is another specific implementation based on the technical solution of Embodiment 1; this embodiment focuses on examining the chemical stability under complex interface environments; the base membrane is a 20µm polyethylene membrane.

[0050] The first inorganic filler is selected from one or more of mesoporous silica, fumed alumina, and boehmite, and the average particle size of the first inorganic filler is 100-500 nm. In the high elasticity buffer layer of this embodiment, the first inorganic filler is entirely made of mesoporous silica, 88 parts, combined with thermoplastic polyurethane binder, 12 parts; the coating thickness is 6 µm, and the drying temperature is 95 °C. The high specific surface area of ​​mesoporous silica enables it to effectively adsorb trace amounts of acidic impurities such as HF generated by electrolyte decomposition, purify the interfacial chemical environment, and inhibit the dissolution and migration of transition metal ions.

[0051] The lithiophilic modifier is selected from one or more of zinc oxide, titanium dioxide, and lithium nitride. The lithiophilic modifier is a nanoparticle grown in situ or coated on the surface of the second inorganic filler by sol-gel method or hydrothermal synthesis. In the high rigidity protective layer of this embodiment, the lithiophilic modifier is a mixture of titanium dioxide and lithium nitride, 1.8 parts, grown in situ on the second inorganic filler, 92.2 parts, and boron nitride: flake alumina = 1.8:1 on the surface; the rigid binder is a mixture of polyvinylidene fluoride and polyimide in a 1:1 ratio, 6 parts; the coating thickness is 3µm, and the drying temperature is 105℃. The design of the composite lithiophilic modifier takes into account both the uniformity of induced deposition and the high efficiency of interfacial charge transport, making the SEI film formed on the surface of lithium metal anode more dense and rich in inorganic components, thus improving the cycle stability of the battery.

[0052] Comparative Example 1

[0053] This comparative example provides a conventional ceramic-coated separator as a blank control for the examples. The separator uses the same 16µm polyethylene-based membrane as in Example 1, but in terms of coating design, only a single layer of alumina ceramic is coated. The coating slurry is composed of 95 parts of ordinary granular alumina with an average particle size of 500nm and 5 parts of polyvinylidene fluoride binder, without containing sheet-like fillers or undergoing lithiophilic modification treatment. The total coating thickness is controlled at 4µm. This comparative example aims to verify the limitations of ordinary ceramic separators in lithium metal batteries when they lack a bilayer gradient structure, a sheet-like physical barrier, and lithiophilic induction function.

[0054] Comparative Example 2

[0055] This comparative example provides a single-layer rigid coated diaphragm lacking a high-elasticity buffer layer; the second ceramic slurry of Example 2 is directly coated on a 16µm polyethylene base film, with a high-rigidity protective layer formulation, and the coating thickness is adjusted to 7.5µm to maintain consistency with the total coating thickness of Example 2; this comparative example aims to verify the necessity of a high-elasticity buffer layer in relieving interfacial stress and preventing the rigid coating from cracking and falling off due to deformation of the base film.

[0056] Comparative Example 3

[0057] This comparative example provides a single-layer elastic coated diaphragm lacking a high-rigidity protective layer; the first ceramic slurry of Example 2 is directly coated on a 16µm polyethylene base film, with a high-elasticity buffer layer formulation and the coating thickness adjusted to 7.5µm; this comparative example aims to verify that if only elastic polymers and ordinary particulate fillers are used, without the physical barrier constructed by high-modulus sheet fillers, the diaphragm will not be able to effectively resist the mechanical penetration of lithium dendrites.

[0058] Comparative Example 4

[0059] This comparative example provides a ceramic-coated separator with a different process path. It uses the exact same raw material formulation as Example 1, but in the preparation of the high-rigidity protective layer, the high-shear exfoliation of the second inorganic filler and the in-situ reaction modification step of the lithium-affinity modifier are omitted. Specifically, commercially available boron nitride powder, flake alumina and nano zinc oxide particles are directly mixed and stirred physically, then prepared into a slurry and coated using a conventional doctor blade, not an extrusion method. This comparative example aims to verify the influence of in-situ growth technology on the uniformity of modifier distribution, as well as the key role of high-shear and extrusion coating processes on the orientation degree of the flake filler and the final physical barrier performance.

[0060] The ceramic-coated separators prepared in Examples 1-5 and Comparative Examples 1-4 were subjected to corresponding physical and electrochemical performance tests. The test results are shown in Table 1. The physical performance tests included the 180° peel strength and bending resistance of the coating and the base film, which characterize the mechanical stability of the coating. The electrochemical performance tests included ionic conductivity, dendrite penetration limiting current density, test in a symmetric cell, and cycle life after assembly into a LiNCM811 full cell, as well as the coulombic efficiency at 1 mA / cm² and after 100 cycles.

[0061] The orientation degree of filler is characterized by the ratio of the diffraction intensity of the 002 crystal plane to that of the 100 crystal plane on the coating surface, which is tested by X-ray diffraction. This ratio, I002 / I100, represents the degree of horizontal orientation of the sheet filler. The larger the value, the better the horizontal orientation.

[0062] Test standards and specific procedures: 1. 180° peel strength: Refer to GB / T2792-2014 standard, use a tensile testing machine to perform peel tests at a speed of 300 mm / min, and repeat the test 5 times for each sample and take the average value; 2. Bending resistance test: Wrap the separator around a round bar with a diameter of 2 mm, and observe whether the coating has cracks or peels off, repeat 3 times; 3. Dendrite puncture limiting current: In Li-Li symmetric cells, increase the current density in steps of 0.5 mA / cm² until the voltage drops suddenly and short-circuits, and record the current density at this time; test 5 cells for each condition and take the average value.

[0063] Table 1: Performance Test Data for Each Embodiment

[0064] As shown in Table 1, Examples 1-5 exhibited significant advantages in all key indicators. Regarding the dendrite suppression mechanism, the dendrite penetration limiting current of the Example group was generally above 8.8 mA / cm², significantly higher than that of Comparative Example 1 (4.0 mA / cm²) and Comparative Example 3 (5.2 mA / cm²). This is mainly attributed to the specific orientation of the sheet-like structure constructed in the high-rigidity protective layer. Comparing Example 1 (85.2% orientation) with Comparative Example 4 (25.4% orientation), it can be seen that although the material composition is the same, without the high-shear peeling and extrusion coating process, the sheet-like filler in Comparative Example 4 could not form an effective horizontal stack, resulting in a significant reduction in the maze effect and a decrease in the limiting current to 6.1 mA / cm². This demonstrates the decisive role of process control in the construction of the microstructure.

[0065] Regarding mechanical adaptability, comparing Example 2 with Comparative Example 2, it can be found that after removing the highly elastic buffer layer, although the coating rigidity is sufficient, the peel strength drops sharply from 22.1 N / m to 10.2 N / m, and severe peeling occurs in the bending resistance test. This confirms the key role of the buffer layer as a stress absorption valve, which effectively alleviates the modulus mismatch between the rigid ceramic layer and the flexible base film during charging and discharging, and prevents the physical failure of the coating.

[0066] Regarding electrochemical stability, the cycle life and coulombic efficiency of the example group were both high. This is because the in-situ grown lithium-loving modifiers, such as zinc oxide and lithium nitride, have a more uniform dispersion scale compared to physical mixing, which can more effectively homogenize the interfacial electric field and induce smooth deposition of lithium ions. Comparative Example 1 performed the worst due to the lack of all the above designs. In summary, this invention successfully solved the contradiction between mechanical protection and interfacial stability in lithium metal batteries through the synergy of a double-layer gradient structure and a specific process.

[0067] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention.

Claims

1. A ceramic-coated separator specifically for lithium metal batteries, characterized in that, It includes a porous polymer-based membrane, wherein one side surface of the porous polymer-based membrane is provided with a composite ceramic coating; The composite ceramic coating has a two-layer gradient structure, including a highly elastic buffer layer in contact with the surface of the porous polymer base film, and a highly rigid protective layer located on the surface of the highly elastic buffer layer and away from the porous polymer base film. The high-elasticity buffer layer is formed by coating and drying a first ceramic slurry, and the high-rigidity protective layer is formed by coating and drying a second ceramic slurry; By weight, the first ceramic slurry comprises: 5-15 parts of elastic polymer binder, 85-95 parts of first inorganic filler, and 100-400 parts of solvent; wherein the total of the elastic polymer binder and the first inorganic filler is 100 parts by weight; by weight, the second ceramic slurry comprises: 3-8 parts of rigid polymer binder, 92-97 parts of second inorganic filler, 0.5-3 parts of lithiophilic modifier, and 100-400 parts of solvent; The first inorganic filler is selected from one or more of mesoporous silica, fumed alumina and boehmite, and the average particle size of the first inorganic filler is 100-500 nm; The second inorganic filler is selected from one or more of boron nitride nanosheets and sheet alumina. The second inorganic filler is a nanosheet structure with an aspect ratio greater than 30 obtained after liquid phase exfoliation and centrifugal classification. The lithiophilic modifier is selected from one or more of zinc oxide, titanium dioxide and lithium nitride. The lithiophilic modifier is a nanoparticle that is grown in situ or coated on the surface of the second inorganic filler by sol-gel method or hydrothermal synthesis.

2. The ceramic-coated separator for lithium metal batteries according to claim 1, characterized in that, The thickness of the highly elastic buffer layer is 3-8µm; the thickness of the highly rigid protective layer is 1-4µm.

3. The ceramic-coated separator for lithium metal batteries according to claim 1, characterized in that, The elastic polymer binder is selected from one or more of styrene-butadiene rubber, hydrogenated nitrile rubber, and thermoplastic polyurethane; The rigid polymer binder is selected from one or more of polyvinylidene fluoride and polyimide.

4. The ceramic-coated separator for lithium metal batteries according to claim 1, characterized in that, The second inorganic filler comprises boron nitride nanosheets and sheet-like alumina, and the mass ratio of the boron nitride nanosheets to the sheet-like alumina is (1:1)-(2:1).

5. A ceramic-coated separator for lithium metal batteries according to claim 1, characterized in that, The porous polymer base membrane is selected from one or more of polyethylene film and cellulose nonwoven fabric, and the thickness of the porous polymer base membrane is 10-25µm.

6. A ceramic-coated separator for lithium metal batteries according to claim 1, characterized in that, The high-elasticity buffer layer is formed by coating and drying the first ceramic slurry after high-speed stirring and ball milling through a micro-gravure coating process. The formation process of the high-rigidity protective layer includes: firstly, subjecting the raw material of the second inorganic filler to high-shear exfoliation dispersion to obtain a sheet-like structure with an aspect ratio greater than 30; the lithiophilic modifier is zinc oxide, titanium dioxide, or lithium nitride nanoparticles grown in situ or coated on the surface of the second inorganic filler by sol-gel method or hydrothermal synthesis method; the second inorganic filler with lithiophilic modifier on the surface and the rigid polymer binder are subjected to high-speed stirring and ultrasonic dispersion treatment to obtain the second ceramic slurry, which is coated and dried using a slot extrusion coating process.

7. A ceramic-coated separator for lithium metal batteries according to claim 6, characterized in that, The drying temperature of the high-elasticity buffer layer is 80-100℃; the drying temperature of the high-rigidity protective layer is 90-110℃.

Citation Information

Patent Citations

  • Composite diaphragm and preparation method thereof and secondary battery

    CN118099667A

  • Double-layer ceramic diaphragm of lithium ion battery

    CN118249041A